Aspects and Modeling of Oscillatory Acid Copper Electroplating. Issue 1 (10th November 2018) - Haubner, Kinga; Fischer, Thomas; Brunner, Heiko; Pohlmann, Ludwig; Donner, Constanze
Abstract : The appearance of galvanostatic oscillation during the deposition of copper from an acid copper bath containing beside the inorganic components, an inhibitor and an accelerator SPS (bis-(sodium sulfopropyl)-disulfide) is described. The inhibitor is a urea-based polymer and acts as a typical leveler (Lev1). The investigation of the adsorption and coadsorption behavior was experimentally done by galvanostatic and potentiostatic injection experiments. The Lev1 and SPS components are both necessary for the temporary potential instability, whereas chloride ions, typical suppressor molecules like PEG 3000 (polyethylene glycol 3000) as well as convection have an influence on the frequency of oscillations and the current range in which oscillations appear, but are not necessarily prerequisite for it. A mathematical model, which describes the preconditions for the occurrence of instabilities, is introduced. The model based on variable potential dependent activities of both the inhibiting leveler (Lev1) and the accelerator component SPS. Potential dependent decomposition rate of the additives is thereby a side effect.